EFFECT OF METACOGNITION AND SELF EFFICACY AGAINST MATHEMATICS LEARNING ACHIEVEMENT THROUGH STUDENT CREATIVITY CLASS XI SMAN IN CITY OF BULUKUMBA - Fathrul Arriah (Universitas Negeri Makassar, 2017)
One of the goals of mathematics lesson at school is that the students were able to solve mathematical problems so that student achievement can be rise. There are several factors that affect students' mathematics achievement, such as metacognition, self-efficacy and creativity of mathematics learning. This study aims to determine how much influence of metacognition and self efficacy against mathematics achievement through creativity of student learning. The study population was a class XI student of SMA in Bulukumba 180 people. The sampling technique by proportional random sampling. Data obtained through questionnaires, then analyzed using descriptive statistics and analysis of SEM (structural equation modeling).The results showed that (1) Metacognition, self efficacy, creativity in learning and mathematics achievement at the high category (2) Effect of metacognition in particular the regulation of metacognition in creativity study is positive and significant; (3) Effect of self efficacy against positive and creative learning is significant; (4) The effect of metacognition in particular metacognitive knowledge on mathematics achievement directly is negative but not significant; (5) Effect of self efficacy against direct mathematics achievement is negative and insignificant; (6) The indirect effect of regulation metacognition particularly in mathematics achievement through learning creativity is a positive and significant; (7) The indirect effect of self-efficacy toward mathematics achievement through learning creativity is positive but insignificant